Financial Stability and Monetary Framework under Interest-Free DSGE Settings for Pakistan - Iqbal, Rao Javaid; Khan, Atiquzzafar; Yasin, Hafiz Muhammad (Islamic Banking and Finance Review, 2023)
Various small and large, conventional and interest-free, DSGE models have been developed, simulated, and compared. After a large conventional model, an interest-free NK model was prepared with household preferences, retail firms, and capital-producing firms. The deduction of zakat was suggested with appropriate incidence. The model was estimated using quarterly data for Pakistan between 1990 and 2009, a period characterized by the consolidation of monetary and macro-prudential policies besides the opening up of the banking sector. This large-scale model included financial accelerator, systemic risk, the inter-bank market, macro-prudential policy, and monetary policy. Both types, that is, interest-based conventional models and interest-free models, were estimated and compared. The welfare loss of four conventional and three interest-free models was computed and compared, where loss decreased with monetary policy and increased with money in utility. The lower value of welfare loss for the large conventional model exhibited effective financial stability policies in Pakistan, as compared to the basic model. It was found that interest-free monetary models couldn’t reduce welfare loss, when compared with conventional models. The study also evaluated three interest-free rates of return as alternatives to interest rates theorized by Khan and Mirakhor (1989). It was found that the shift towards an interest-free regime for entrepreneurs, banking, inter-bank operations, central banking, and policies can be simulated with Pakistan’s data. The Islamic model showed lesser convergence, so the fit of the model was reduced.